2020
DOI: 10.1037/pag0000582
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness is associated with less amyloid deposition in cognitively normal aging.

Abstract: Little is known about the association between personality and Alzheimer's disease (AD) biomarkers, and existing results are inconsistent. We aimed to determine whether personality was associated with ␤-amyloid (A␤) accumulation in cognitively normal aging. One hundred twenty-nine participants were included in this cross-sectional study. Personality was measured with the Big Five Inventory (BFI) and brain A␤ deposition was assessed with [ 11 C] Pittsburgh compound B (PiB)-positron emission tomography (PET) imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It has been well established that the pathological sequalae of dementia such as changes in brain structure and accumulation of amyloid plaques are known to begin up to two decades before the onset of cognitive disturbances (Bateman et al, 2012). Additionally, recent studies have found associations between FFM personality traits and Alzheimer's neuropathology (Aschenbrenner et al, 2020;Yoon et al, 2020). Therefore, we cannot make strong conclusions regarding the directionality of the relationship between personality and cognitive status based on the results of this study.…”
Section: Strengths and Limitationsmentioning
confidence: 63%
“…It has been well established that the pathological sequalae of dementia such as changes in brain structure and accumulation of amyloid plaques are known to begin up to two decades before the onset of cognitive disturbances (Bateman et al, 2012). Additionally, recent studies have found associations between FFM personality traits and Alzheimer's neuropathology (Aschenbrenner et al, 2020;Yoon et al, 2020). Therefore, we cannot make strong conclusions regarding the directionality of the relationship between personality and cognitive status based on the results of this study.…”
Section: Strengths and Limitationsmentioning
confidence: 63%
“…In addition, individuals with a high level of conscientiousness have consistently been lower BMI and gained less weight over time, particularly during major life transitions [23]. It also suggests that this trait is linked to healthier biomarker profiles and improved physical functioning [24,25]. The most essential health-related activities, particularly physical exercise habits and healthy eating behavior, are reliably predicted by conscientiousness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, purpose in life 9 and the personality characteristic conscientiousness 10 have been associated with markedly reduced AD incidence. Novel neuroimaging and clinicopathologic findings have demonstrated that purpose in life 11 and conscientiousness, 12 among other psychological characteristics (e.g., resilience to stress, 13 optimism, 14 and trait mindfulness 15 ), may bestow protective benefit. Specifically, higher levels of conscientiousness and trait mindfulness and greater resilience to stress have been associated with less amyloid deposition and/or tau aggregation.…”
Section: Trial Registration Informationmentioning
confidence: 99%